Open defecation practice among households with latrines in rural communities of Ararso District, Somali Region, Eastern Ethiopia - Ismail, Abdifatah Mohamud; Ibrahim, Musse Ahmed; Abdi, Mahammoud Mohammed; Geremew, Abraham; Mulugeta, Yohannes; Ayele, Dinku Mekbib; Cheru, Abera (Frontiers in Public Health, 2024)
Background Open defecation contributes to the spread of different feco-oral diseases. Therefore, access to a latrine is strongly recommended, as it considerably reduces the risks. Even though provision of latrine facilities alone does not guarantee the desired health benefits, they should be integrated with behavior change. In Ethiopia, efforts have been made to increase the coverage of latrine facilities. However, evidence on how consistently households use it is limited. Most prior studies focused on latrine utilization among households, and limited evidence is available about open defecation practices among households with latrines and associated factors. Thus, this study is critical for developing effective intervention approaches to prevent open defecation among households with latrines. Objective The aim of this study was to assess the open defecation practice and associated factors among households with latrines in rural communities of Ararso District, Somali Region, Eastern Ethiopia, 2023. Method A community-based, cross-sectional study design was employed among households with latrines in the district. A total of 632 households latrines were selected using a systematic sampling technique. Data were collected using a structured questionnaire and an observational checklist. The questionnaire was designed in KoboTool box, Humanitarian Response software, and the data were collected using the Kobo Collect version 2023.2.4 mobile application. The data were downloaded from the server in the Microsoft Excel format for data cleaning before being exported to STATA version 14 for analysis. Bivariate and multivariable analyses were employed to investigate the relationship between outcome and independent variables. Odd ratios with 95% confidence intervals were utilized to assess the association between the outcome and the predictor variables. A P-value of <0.05 was used as the threshold point for statistical significance. Result In this study, the prevalence of open defecation practice among households with latrines was 32.4% (95% CI: 28.1, 35.9). Sex of the household (AOR = 1.60, 95% CI: 1.06, 2.4), educational status (AOR = 2.40, 95% CI: 1.08, 5.53), family size (AOR = 1.62, 95% CI: 1.22, 2.78), the presence of under-5-year-old children in the house (AOR = 1.84, 95% CI: 1.19, 2.75), the need for latrine maintenance (AOR = 2.37.95% CI: 1.62, 3.48), current status of the latrine (AOR = 2.37, 95% CI: 1.62, 3.48), and latrine cleanness status (being unclean) (AOR = 1.91, 95% CI: 1.29, 2.81) were significantly associated with open defecation practice among households with latrine. Conclusion The study concluded that open defecation was significantly practiced by households with latrines. This revealed that the presence of a latrine alone was insufficient to considerably reduce open defecation. To alleviate this problem, the government and health workers, in collaboration with the health bureau, should promote frequent sanitation and hygiene education in the communities.